POTENSI VAKSIN ATEROSKLEROSIS VIA INDUKSI PROTEIN LECTIN-LIKE OXIDIZED LDL RECEPTOR 1 (LOX-1) TERHADAP AKTIVASI NF-κB, EKSPRESI eNOS DAN KADAR CRP PADA TIKUS DENGAN DIET ATEROGENIK - Albaar, Thoha Muhajir; Tamara, Fredo; A, Oktavia Rahayu; Putri, Ardina Pramesti; Nurkhairina, Angi; Yurina, Valentina (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Atherosclerosis is a chronic inflammation condition as a response to the lipoproteins deposition in the artery wall.Oxidized low density lipoprotein (OxLDL) the major of atherosclerosis development. Lectin- like oxidized lo density lipoprotein 1 (LOX-1) is primary receptor for OxLDL in endothelial cells. Recent studies have shown that LOX-1 might be potential for the atherosclerosis drugs development. This study was designed to investigate the response of LOX-1 vaccination with alum as adjuvant for atherogenesis to prevent increasing of NF-kB , CRP, and decrease of eNOS. This study was experimental laboratory with post test only control group design for 56 days using 28 male Wistar rats. Rats were divided into 7 groups which were negative control with normal diet AIN 93 M, positive control with atherogenic diet AIN 93 M, atherogenic diet AIN 93 M and LOX-1 protein treatment with dosage 1 ng + alum (P1), 10 ng + alum (P2), 100 ng + alum (P3), 1μg + alum (P4) and alum only (P5). On the 57th day, the rats were sacrificed and taken its serum spesimen to measure CRP level with enzyme immunoassay method and aorta tissues to measure NF-kB activation and expression eNOS with immunohistochemical method. Statistical analysis showed that the administration of LOX-1 protein in the treatment groups is significant to prevent NF-kB activation (p=0,00) and prevent decreased expression of eNOS (p=0,00), but not significant to prevent increased CRP level (p=0,83). The conclusion of this study is that the LOX-1 protein vaccination have potency to prevent atherosclerosis with decreasing NF-kB activation and prevent decreasing eNOS expression. Keywords: Atherosclerosis vaccine, LOX-1, NF-kB, eNOS, CRP